PENGARUH WORD OF MOUTH DAN CUSTOMER COMMUNITY TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA VIXION DI BANGKINANG - Alpita, Rizka; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Bangkinang City, and the purpose of this study was to determine the effect of word of mouth and customer community on buying decisions in Bangkinang City. The population in this study were all members of the community Yamaha Vixion Club (YVC) Bangkinang as many as 30 people. Samples were determined in this study are determined by census techniques, ie sampling technique when all members of the population used as a sample. The data used are primary data and secondary data. Data analysis method used is descriptive quantitative method.The results showed a partial word of mouth significant influence on purchasing decisions Yamaha motorcycle Vixion in Bangkinang City. While the customer community have a significant effect on purchasing decisions Yamaha motorcycle Vixion in Bangkinang City.Simultaneously, this research shows that word of mouth and customer community is besama both significantly influence purchasing decisions Yamaha motorcycle Vixion in Bangkinang City. R value of 0.890 means the closeness of the relationship between the dependent variable and independent variables is very strong. Adjusted R Square value of 0.778, which means word of mouth (X1) and customer community (X2) significantly by 77.8% on purchasing decisions Yamaha motorcycle Vixion in Bangkinang City, while the rest (100% - 77.8% = 22 , 2%) are influenced by factors - other factors.Keywords: Word of Mouth, Customer community, buying decision